Self-Care and Quality of Life of Ostomy Patients: A Structural Equation Modeling Analysis - Ilaria Marcomini; Paolo Iovino; Laura Rasero; Duilio Fiorenzo Manara; Ercole Vellone; Giulia Villa (Nursing Reports)
Background. Previous research has shown that patients with ostomy frequently exhibit a low health-related quality of life (HRQoL). Self-care is a key element that influences their HRQoL. However, the evidence regarding the relationship between these two constructs in patients with ostomy is still not clear. Materials and Methods. This was a secondary analysis of an Italian multicenter, observational, longitudinal study. Participants were recruited from seven outpatient ostomy care clinics in central and northern Italy. The Stoma-Specific Quality of Life Questionnaire (Stoma QoL) and the Ostomy Self-Care Index (OSCI) were administered to the participants. The relationship between self-care and HRQoL was analyzed using structural equation modeling. Results. A total of 521 patients were enrolled. Our results emphasized that self-care is a predictor of HRQoL among people with ostomy. Self-care maintenance and self-care monitoring had a positive effect on HRQoL (self-care maintenance: β = 0.506, p < 0.001; self-care monitoring: β = 0.303, p < 0.001). The model exhibited acceptable fit indices: χ2 (151, n= 521) = 516.447, p ≤ 0.001, comparative fit index (CFI) = 0.97, Tucker–Lewis index (TLI) = 0.96, root mean square error of approximation (RMSEA) = 0.068 (90% CI, 0.062–0.075), p < 0.001, and standardized root mean square residual (SRMR) = 0.038. Conclusions. The structural equation model tested the causal relationship between self-care and HRQoL in people with a stoma, demonstrating for the first time that inadequate self-care in patients with ostomy may lead to lower HRQoL. Thus, to enhance HRQoL, interventions should be designed to improve self-care behaviors. Future research should investigate potential mediating variables in the relationship between self-care and HRQoL.